Critical Discourse Analysis on Prabowo Subianto’s Presidential Inauguration Speech - Mukminin, Muhamad Saiful; Alya, Nanda Nursa; Indiraphasa, Nuriel Shiami; Wulandari, Ni Wayan Novi; Prasetya, Kabul (Journal of Language, Literature and Teaching, 2024)
This study examines Prabowo Subianto's presidential inauguration speech using Norman Fairclough's Critical Discourse Analysis (CDA) to explore how language shapes and is influenced by power and ideology in the context of Indonesian politics. A qualitative approach with a descriptive method is employed to provide a deep, comprehensive analysis of the speech text, without altering its original meaning. The data for this study is the text of Prabowo Subianto’s inauguration speech, sourced from official transcripts or recordings. Data collection involves observation and documentation, while data analysis utilizes the three CDA dimensions, i.e. textual analysis, discourse practice, and social practice. The findings reveal that the speech is structured to emphasize gratitude, a national vision, and a call for unity, using inclusive language and repetition to foster a sense of national responsibility. The discourse analysis shows that Prabowo’s speech aims to build a positive, inclusive image and reach a broad audience through media distribution. Socially, the speech positions Indonesia as a strong, independent nation, with Prabowo portraying himself as a leader committed to democratic values and national unity. The study concludes that the speech effectively constructs a political identity based on inclusivity, responsibility, and unity.